2014
DOI: 10.1111/aji.12214
|View full text |Cite
|
Sign up to set email alerts
|

Differential Glucocorticoid Receptor‐Mediated Effects on Immunomodulatory Gene Expression by Progestin Contraceptives: Implications for HIV‐1 Pathogenesis

Abstract: Whether hormonal contraceptives increase HIV‐1 acquisition, transmission and disease progression are critical questions. Clinical research has been hampered by a lack of understanding that different progestins used in contraception exhibit differential off‐target effects via steroid receptors other than the progesterone receptor. Of particular, relevance is the relative effects of medroxyprogesterone acetate (MPA) and norethisterone enanthate (NET‐EN), widely used as injectable contraceptives in sub‐Saharan Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
3
40
1
Order By: Relevance
“…Studies using non-human primate models demonstrated that DMPA enhances the risk of simian immunodeficiency virus (SIV) acquisition via vaginal exposure (reviewed in 7,13 ). Medroxyprogesterone acetate (MPA), the contraceptive component of DMPA, was shown to suppress systemic regulators of cellular and humoral immunity, reduce cytokine production by plasmacytoid dendritic cells (pDCs), and increase the replication of HIV-1 in activated peripheral blood mononuclear cells (PBMCs) in vitro 28-32 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using non-human primate models demonstrated that DMPA enhances the risk of simian immunodeficiency virus (SIV) acquisition via vaginal exposure (reviewed in 7,13 ). Medroxyprogesterone acetate (MPA), the contraceptive component of DMPA, was shown to suppress systemic regulators of cellular and humoral immunity, reduce cytokine production by plasmacytoid dendritic cells (pDCs), and increase the replication of HIV-1 in activated peripheral blood mononuclear cells (PBMCs) in vitro 28-32 .…”
Section: Introductionmentioning
confidence: 99%
“…Medroxyprogesterone (MPA), for example, has androgenic activity, no anti-mineralocorticoid activity and potent glucocorticoid activity, higher than any other progestogen or endogenous progesterone. Activation of glucocorticoid receptors, seen with MPA, may influence glucocorticoid-like immunosuppressive effects on genes involved with immune function [86, 87]. These differences between contraceptives warrant further investigation and may influence relative contraceptive safety.…”
Section: Potential Biologic Mechanisms For Increased Hiv Acquisition mentioning
confidence: 99%
“…Further studies are needed for a better comprehension of the many and complex effects of progesterone and other steroid hormones on melanoma and other cancers. This need is made urgent especially when considering that progesterone and its synthetic progestin analogs are clinically employed as methods of contraception and in hormone replacement therapies [42][43][44][45][46][47], in the treatment of recurrent miscarriage and during assisted reproductive technologies [48]. A higher caution in the clinical use of progesterone is thus mandatory, since PG concentrations capable of stimulating melanoma cell proliferation are very close to the pharmacological doses of PG commonly used in a wide spectrum of physio-pathological conditions.…”
Section: Discussionmentioning
confidence: 99%